2018
DOI: 10.1039/c8en00325d
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic, metabolic and macromolecular response of bacteria to chronic nanoparticle exposure in continuous culture

Abstract: Effect of specific growth rates on metabolic and macromolecular response of bacteria to chronic antimicrobial nanoparticle exposure are studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 48 publications
0
34
0
Order By: Relevance
“…Studies utilizing similar delayed exposure protocols have also yielded a decrease in the stationary phase when S. oneidensis MR-1 was exposed to chromium(VI) and E. coli to silver nanoparticles (AgNPs). 31,32 Previous work has shown that NMC toxicity to S. oneidensis MR-1 is related to its dissolution and release of ions, particularity nickel and cobalt, into the growth media. 12 Although some of these metals are micronutrients, metal homeostasis of the organism is disturbed at higher concentrations of nickel and copper, which could cause oxidative stress, the replacement of the native metal cofactor of some proteins, or the binding of metals with critical functional groups on proteins or nucleic acids.…”
Section: Resultsmentioning
confidence: 99%
“…Studies utilizing similar delayed exposure protocols have also yielded a decrease in the stationary phase when S. oneidensis MR-1 was exposed to chromium(VI) and E. coli to silver nanoparticles (AgNPs). 31,32 Previous work has shown that NMC toxicity to S. oneidensis MR-1 is related to its dissolution and release of ions, particularity nickel and cobalt, into the growth media. 12 Although some of these metals are micronutrients, metal homeostasis of the organism is disturbed at higher concentrations of nickel and copper, which could cause oxidative stress, the replacement of the native metal cofactor of some proteins, or the binding of metals with critical functional groups on proteins or nucleic acids.…”
Section: Resultsmentioning
confidence: 99%
“…Faghihzadeh et al showed that acute and chronic exposure to AgNPs causes genetic and phenotypic changes in E. coli, which ultimately leads to resistance [ 81 ]. One of the changes observed by the authors was a modification of composition and amount of EPS secreted by E. coli .…”
Section: Interactions Involved In Biofilm Resistance To the Nanopamentioning
confidence: 99%
“…One of the changes observed by the authors was a modification of composition and amount of EPS secreted by E. coli . Specifically, through up-regulation of capsular polysaccharide regulon gene ( cpsB gene), the amount of biofilm polysaccharides was increased after exposure to AgNPs [ 81 ]. Additionally, the ATP-dependent efflux of silver was also increased due to overexpression of copper transporter gene ( copA gene).…”
Section: Interactions Involved In Biofilm Resistance To the Nanopamentioning
confidence: 99%
“…These ECS were able to modify the size and zeta potential of the nanoparticles by causing their agglomeration. In addition, the composition of the ECS depended on the growth conditions used [17]. On the other hand, the interaction of the nanoparticles in pathophysiological environments leads to the formation of biomolecule coronas (similar to the ECS) around the nanoparticles that prevent their contact with the pathogens and decrease their bactericidal activity [18].…”
Section: Defense Mechanisms Against Different Sizes Of Metal and Mmentioning
confidence: 99%